Effect of lupin flour incorporation on the physical and sensory quality of pasta - Jayasena, Vijay; Nasar-Abbas, Syed (Department of Agriculture and the Grains Research & Development Corporation, 2011)
Key Message: Nutritional value of pasta in terms of protein and dietary fibre contents can be significantly increased by incorporating 20% lupin flour without deteriorating its physical and sensory properties.